Proceedings of the 2015 Internet Measurement Conference 2015
DOI: 10.1145/2815675.2815710
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Interference between Measurements on the RIPE Atlas Platform

Abstract: Public measurement platforms composed of low-end hardware devices such as RIPE Atlas have gained significant traction in the research community. Such platforms are indeed particularly interesting as they provide Internet-wide measurement capabilities together with an ever growing set of measurement tools. To be scalable though, they allow for concurrent measurements between users. This paper answers a fundamental question for any platform user : Do measurements launched by others impact my results ? If so, wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 13 publications
0
14
1
Order By: Relevance
“…Although past research has shown that v1 and v2 probes can be less reliable [13], in our experiments we observe only slight differences in our aggregated results when using these probes. As a trade-off between precision and coverage, we avoid using these probes when it is not needed ( §4) but we include them when surveying last-mile latency at large scale ( §3).…”
Section: From Traceroute To Last-mile Congestioncontrasting
confidence: 82%
“…Although past research has shown that v1 and v2 probes can be less reliable [13], in our experiments we observe only slight differences in our aggregated results when using these probes. As a trade-off between precision and coverage, we avoid using these probes when it is not needed ( §4) but we include them when surveying last-mile latency at large scale ( §3).…”
Section: From Traceroute To Last-mile Congestioncontrasting
confidence: 82%
“…This is the basic insight behind the measurement of in-network buffering performed by Netalyzr [34] and other measurement platforms, and has been used more recently in the inference of congestion at network interconnects [35]. Load on the endpoint can also be visible in RTT measurements, as shown by Holterbach et al [36], who showed in a study of the load dependent accuracy of the Atlas platform that several milliseconds of RTT error could be induced and measured by varying the load on RIPE Atlas probes.…”
Section: Load Telemetrymentioning
confidence: 97%
“…• RIPE Atlas [19], [27] is a global network of probes that measure Internet connectivity and reachability, and is primarily deployed by home users to provide an understanding of the state of the commercial Internet (not R&E networks) in real time.…”
Section: Related Workmentioning
confidence: 99%